Pengembangan Media Pembelajaran Interaktif pada Materi Fotosintesis di Kelas IV Sekolah Dasar - Utami, Dinda Putri; Alpusari, Mahmud; Kurniaman, Otang (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
This research aims to develop a valid and practical product of interactive learning media on photosynthesis subject in grade IV elementary school. The method used in this research is the Research and Development using the ADDIE model. This ADDIE model has 5 stages, namely: Analysis, Design, Development, Implementation and Evaluation. In developing this interactive learning media, the developed subject were then validated by 3 validators consisting of media expert, subject expert and linguist. To see the practicality of the developed media, the researcher conducted a limited trial which is a small group trial with teachers and students. The data collection techniques used in this research were interviews, observations and questionnaires. Analysis techniques used by the researcher was descriptive qualitative analysis and quantitative analysis. Based on the validity test results, it was found that the developed interactive learning media got a highly valid category with a percentage score of 85,05%, where as the practicality of interactive learning media based on the teacher response practicality questionnaire was 88,7% with very valid criteria and based on the student response practicality questionnaire was 94,09% with very valid criteria. Based on the research findings, it can be concluded that the interactive learning media on photosynthesis subject in grade IV elementary school has met the valid and practical criteria so that it can be used by teachers and students in the learning process.